Effectiveness of diterpene ginkgolides meglumine injection after endovascular therapy for cardioembolic stroke: a randomized controlled trial - Li, Yiping; Zhou, Kun; Wei, Jianan; Fu, Xinmin (Frontiers in Pharmacology, 2026)
BackgroundEndovascular interventional therapy is an important treatment method for cardioembolic stroke. Diterpene Ginkgolides Meglumine Injection (DGMI) may serve as an adjunct to endovascular interventional therapy for acute ischemic stroke.MethodsPatients with cardioembolic stroke receiving endovascular treatment were recruited and randomly assigned in a 1:1 ratio to either the DGMI treatment group or the control group. After the procedure, all patients routinely received management of risk factors and standard medication. Patients in the treatment group additionally received DGMI 25 mg diluted in 250 mL normal saline, administered by intravenous drip once daily for 14 consecutive days. NIHSS scores, modified Rankin Scale (mRS) scores, and hematologic parameters were measured, with adverse reactions monitored throughout.ResultsA total of 104 patients completed the study. After 14 days of treatment, HCT was significantly lower and PT was significantly higher in the treatment group ((p = 0.032 and p = 0.049, respectively). NIHSS and mRS scores in the treatment group were significantly lower than those in the control group at 14 days (p = 0.043 and p = 0.009, respectively). Similarly, the mRS score at 90 days was significantly lower in the treatment group (p = 0.009). The logistic regression analysis revealed that both group assignment and baseline NIHSS score were significantly associated with ΔNIHSS. A lower preoperative NIHSS score was associated with greater neurological improvement (OR = 0.893, 95% CI = 0.819–0.974, p = 0.011). Additionally, the DGMI group demonstrated superior effectiveness compared to the control (OR = 3.490, 95% CI = 1.077–11.316, p = 0.037).ConclusionThe combination of DGMI with endovascular therapy in patients with cardioembolic stroke is associated with reduced levels of coagulation biomarkers, improved neurological function, and better long-term prognosis, suggesting its potential as a complementary treatment following interventional procedures in clinical practice.